(3GdhGajI aj TQM GdcGajIs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s
(3ChdgG (B:s
(3hHYO aEfi UGjZ ai gPG GdQbje ef aQGjO GdeYGfi eGMhG Hg aj GdYbO GdfXje s
(3BNQgG (B:s
(3hbO hSeJg HYO aQGZg hMUhdg eG jMbb MSf eSGZI HGdehGQO GdhQjI GdUGajI ai TQM GdcGajI GdhGajI s
(3GdcGajI dGHf GdMGLH GfXQ cTa GdXfhf L(B2 (3U` (B1370s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas